2012
DOI: 10.1068/i0430
|View full text |Cite
|
Sign up to set email alerts
|

Illusory Object Motion in the Centre of a Radial Pattern: The Pursuit-Pursuing Illusion

Abstract: A circular object placed in the centre of a radial pattern consisting of thin sectors was found to cause a robust motion illusion. During eye-movement pursuit of a moving target, the presently described stimulus produced illusory background-object motion in the same direction as that of the eye movement. In addition, the display induced illusory stationary perception of a moving object against the whole display motion. In seven experiments, the characteristics of the illusion were examined in terms of luminanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 92 publications
(161 reference statements)
0
17
0
Order By: Relevance
“…However, illusion classification did not reach a general consensus yet (see Hamburger, 2016 , for a recent review). Measuring a visual illusion, even if it sounds counterintuitive, can be done in a very accurate way in both human and non-human species (e.g., Macknik and Livingstone, 1998 ; Conway et al, 2005 ; Gori et al, 2006 , 2008a , 2010a , b , 2014 ; Fantoni and Pinna, 2008 ; Giora and Gori, 2010 ; Gori and Spillmann, 2010 ; Spillmann et al, 2010 ; Hamburger, 2012 ; Ito, 2012 ; Otero-Millan et al, 2012 ; Shi et al, 2013 ; Agrillo et al, 2015 ). Following the everyman’s perspective, visual illusions could not be considered a good tool for investigating perceptual differences in groups because they are “subjective”.…”
Section: Visual Illusion As a Tool To Investigate Brain Processingmentioning
confidence: 99%
“…However, illusion classification did not reach a general consensus yet (see Hamburger, 2016 , for a recent review). Measuring a visual illusion, even if it sounds counterintuitive, can be done in a very accurate way in both human and non-human species (e.g., Macknik and Livingstone, 1998 ; Conway et al, 2005 ; Gori et al, 2006 , 2008a , 2010a , b , 2014 ; Fantoni and Pinna, 2008 ; Giora and Gori, 2010 ; Gori and Spillmann, 2010 ; Spillmann et al, 2010 ; Hamburger, 2012 ; Ito, 2012 ; Otero-Millan et al, 2012 ; Shi et al, 2013 ; Agrillo et al, 2015 ). Following the everyman’s perspective, visual illusions could not be considered a good tool for investigating perceptual differences in groups because they are “subjective”.…”
Section: Visual Illusion As a Tool To Investigate Brain Processingmentioning
confidence: 99%
“…The FD illusion is a visual illusion that was first described by Kelly (1966) . Measuring a visual illusion, even if it sounds counterintuitive, can be done in a very accurate way (e.g., Gori et al, 2006 , 2008 , 2011 ; Yazdanbakhsh and Gori, 2008 ; Giora and Gori, 2010 ; Gori and Spillmann, 2010 ; Ito, 2012 ). The FD illusion appears to be dependent on the spatial and temporal frequency of a flickering grating.…”
Section: Introductionmentioning
confidence: 99%
“…It was also suggested that very small eye movements called microsaccades have an important role to play in the perception of shimmering [ 18 ]. Empirical evidence has been found to support this claim in the case of the Enigma illusion [ 19 ], as well as other illusions of motion based on geometric patterns [ 20 ][ 21 ][ 22 ].…”
Section: Introductionmentioning
confidence: 95%